2020
DOI: 10.21203/rs.3.rs-24745/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Klotho inhibits H 2 O 2 -induced oxidative stress and apoptosis in periodontal ligament stem cells by regulating UCP2 expression

Abstract: Background Periodontitis, known as a human chronic inflammatory disease, has affected the life of millions of individuals. Known risk factors such as metabolic disease and oxidative stress have been reported to be closely associated with the initiation or development of periodontitis. However, the etiology of periodontitis remains unclear. Klotho, a single-pass transmembrane protein, has been widely reported to modulate cellular processes in various diseases. However, the role of Klotho in periodontitis is unk… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that α-KL is not only involved in the regulation of calcium and phosphorus metabolism and the inhibition of renal fibrosis in CKD (7,8), but as an in-vivo hormone, it also exerts anti-oxidative stress, anti-inflammatory, anti-apoptotic, and autophagy-regulating effects (9)(10)(11)(12). Under normal renal physiological conditions, α-KL, fibroblast growth factor receptor-1 (FGFR1) and fibroblast growth factor-23 (FGF23) bind to form a trimeric complex, which drives FGF23 phosphorylation and thus reduces serum Pi by inhibiting 1,25-dihydroxyvitamin D and parathyroid hormone synthesis, intestinal Pi absorption, and Pi reabsorption (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that α-KL is not only involved in the regulation of calcium and phosphorus metabolism and the inhibition of renal fibrosis in CKD (7,8), but as an in-vivo hormone, it also exerts anti-oxidative stress, anti-inflammatory, anti-apoptotic, and autophagy-regulating effects (9)(10)(11)(12). Under normal renal physiological conditions, α-KL, fibroblast growth factor receptor-1 (FGFR1) and fibroblast growth factor-23 (FGF23) bind to form a trimeric complex, which drives FGF23 phosphorylation and thus reduces serum Pi by inhibiting 1,25-dihydroxyvitamin D and parathyroid hormone synthesis, intestinal Pi absorption, and Pi reabsorption (13,14).…”
Section: Introductionmentioning
confidence: 99%